The Use of Home Spirometry in Pediatric Cystic Fibrosis Patients: Results of a Feasibility Study. (2nd February 2017) - Shakkottai, Aarti; Nasr, Samya Z.
Medication adherence is poor among pediatric cystic fibrosis (CF) patients, with adolescents having one of the lowest adherence rates. We wanted to identify an adherence intervention that would be acceptable to CF adolescents and assess its feasibility. We surveyed 40 adolescents with CF and asked about barriers to and motivators for their own adherence and to generate ideas for potential adherence interventions. Since most of the respondents chose frequent spirometry at home and medication reminders for interventions, we selected 5 subjects, 10 to 14 years of age, with CF to test the feasibility of home spirometry and medication reminders in pediatric CF patients. This article summarizes the results of both the survey and the feasibility pilot study.